Occupational exposure and effects on the male reproductive system - Erika Kaltenecker Retto de Queiroz; William Waissmann
A significant increase in the incidence of male infertility has been described in the international literature, raising questions about its causes. Part of this effect may result from synthetic toxic substances acting on the endocrine system (endocrine disruptors), many of which are routinely used in work processes. We provide a critical review of the specialized literature on work-related chemical substances capable of causing male infertility. Pesticides such as DDT, linuron, and others, heavy metals like mercury, lead, cadmium, and copper, and substances from various industrial uses and residues such as dioxins, polychlorinated biphenyls (PCBs), ethylene dibromide (EDB), phthalates, polyvinyl chloride (PVC), and ethanol are among the main endocrine disruptors that can cause male infertility. Based on the literature, gonadal dysfunction and congenital malformation are the main alterations caused by these substances in the male reproductive system. We conclude that despite the relative lack of studies on this issue, the relevance of such risk calls for further studies as well as measures to prevent workers' exposure to the various substances.